Fishery Industry Development in Morotai Island Regency: A Scientific Concept for Integrated Economics Model - Achmad Zamroni; Siti Hajar Suryawati; Andrian Ramadhan; Sonny Koeshendrajana (JURNAL PERIKANAN DAN KELAUTAN, 2019)
The development of the fisheries industry in Morotai Island District faces major challenges in investment climate recently. Those investment is influenced by fisheries resources, infrastructure, markets and institutions. This paper aims to describe the fishery industry in Morotai Island District, analyze the concept of the fishery industry model, and formulate a strategy for economic integration. Primary data was taken using a structured questionnaire through interviews with respondents and focused group discussions (FGD). The primary information is supplemented by secondary data obtained from district statistical data, research reports, and related scientific publications. Data were analyzed using four methods, namely: descriptive analysis; Analysis of Strengthen, Weakness, Opportunity and Threat (SWOT); Quantitative Strategic Planning Matrix (QSPM) analysis; and MIC-MAC analysis. The results from the analysis show the integrated marine and fisheries center (SKPT) policy implementation has had a positive effect on the fisheries industry development in Morotai Island. There are four main influence aspects: (1) marine and fisheries resources (SDKP) management; (2) economic and business development; (3) community development; and (4) regulatory and synergies. The strategy of economic integration is focused on the implementation of the fisheries industry model as the production and export base for fresh tuna.